Why is the number of days required for induction of adult diapause in the linden bug Pyrrhocoris apterus fewer in the larval than in the adult stage?. (June 2015) - Hodkova, Magdalena
Graphical abstract: Highlights: Adult diapause is expressed in adults, but may be programmed in larvae. Diapause programming requires fewer pro-diapause short days in larvae than in adults. In larvae, some diapause 'information' is present also in anti-diapause long days. In larvae kept continuously in long days, diapause 'information' decreases. Diapause 'information' is maintained in darkness (neutral condition). Abstract: Adult females of Pyrrhocoris apterus, programmed for diapause by short-day (SD) photoperiod and those programmed for reproduction by long-day (LD) retain photoperiodic information in continuous darkness (DD) until death. However, if the interruption of SD by DD is made in the course of diapause programming in adults, then the incidence of diapause depends on the number of SD cycles received before DD, with no evidence that the photoperiodic clock is free-running at DD to complete diapause induction. These results indicate that the photoperiodic clock is stopped after transfer to DD and the information accumulated before transfer to DD is maintained. Diapause programming in the adult stage requires 9–10 SD cycles to induce diapause in 80% of individuals. However, if the diapause programming starts after ecdysis of LD-larvae to the last instar, only 3 SD cycles before transfer to DD are required for diapause in 80% of individuals. Surprisingly, if the newly ecdysed last instar LD-larvae, sensitive to photoperiod, are transferred to DD (thus they did not experience any SD), diapause occurs in 40% of the individuals. Thus, diapause 'information' is present in LD-larvae and is responsible for a lower number of SD required for diapause induction in the larval than in the adult stage.